Laboratory Studies of Nonlinear Optical Signals for Caries Detection. (May 2016) - Terrer, E.; Panayotov, I.V.; Slimani, A.; Tardivo, D.; Gillet, D.; Levallois, B.; Fejerskov, O.; Gergely, C.; Cuisinier, F.J.G.; Tassery, H.; Cloitre, T.
Multiphoton confocal microscopy and nonlinear spectroscopy are used to investigate the caries process in dentin. Although dentin is a major calcified tissue of the teeth, its organic phase comprises type I collagen fibers. Caries drive dentin demineralization and collagen denaturation. Multiphoton microscopy is a powerful imaging technique: the biological materials are transparent to infrared frequencies and can be excited to penetration depths inaccessible to 1-photon confocal microscopy. The laser excitation greatly reduces photodamage to the sole focal region, and the signal-to-noise ratio is improved significantly. The method has been used to follow pathologic processes involving collagen fibrosis or collagen destruction based on their 2-photon excited fluorescence (2PEF) emission and second harmonic generation (SHG). Combining multiphoton imaging with nonlinear spectroscopy, we demonstrate that both 2PEF and SHG intensity of human dentin are strongly modified during the tooth caries process, and we show that the ratio between SHG and 2PEF signals is a reliable parameter to follow dental caries. The ratio of the SHG/2PEF signals measured by nonlinear optical spectroscopy provides valuable information on the caries process, specifically on the degradation of the organic matrix of dentin. The goal is to bring these nonlinear optical signals to clinical application for caries diagnosis.